Patients’ IgLON5 autoantibodies interfere with IgLON5-protein interactions - Landa, Jon; Serafim, Ana Beatriz; Gaig, Carles; Saiz, Albert; Koneczny, Inga; Hoftberger, Romana; Santamaria, Joan; Dalmau, Josep; Graus, Francesc; Sabater, Lidia (Frontiers in Immunology, 2023)
Abstract Background: Anti-IgLON5 disease is a rare neurological disorder characterized by autoantibodies against IgLON5, and pathological evidence of neurodegeneration. IgLON5 is a cell adhesion molecule but its physiological function is unknown. Our aim was to investigate the IgLON5 interactome and to determine if IgLON5 antibodies (IgLON5-abs) affect these protein interactions. Methods: IgLON5 interactome was investigated by mass spectrometry sequencing of proteins immunoprecipitated by IgLON5 autoantibodies using cultures of rat cerebellar granular neurons (CGNs). Shedding of IgLON5 was explored using HEK cells transfected with human IgLON5 plasmid and in CGNs. Interactions of IgLON5 with identified binding partners and IgLON5-abs effects were confirmed by immunofluorescence in transfected HEK cells and rat hippocampal neurons. Results: Patients’ IgLON5 antibodies co-precipitated all members of the IgLON5 family and three 3 additional surface proteins. IgLON5 predominantly establishes homomeric and heteromeric cis (within the cell) and trans (between cells)-interactions with other IgLON family members and undergoes spontaneous ectodomain shedding. Antibodies from patients with anti-IgLON5 disease prevent trans-interactions in hippocampal neurons independently of the IgLON5 IgG subclass distribution. Conclusions: We show a potentially novel pathogenic mechanism of IgLON5-abs that consists in blocking IgLON5 interactions with its binding partners. These findings extend our knowledge about the physiological role of IgLON5 and pave the way to future understanding of the pathological mechanisms of anti-IgLON5 disease.